Analyzing the Job Rotation Factors for the Education Organizational in Malaysia - Maizura Abd Rashid, Intan; Ahmad Fauzi Wan Husain, Wan; Hanie Abu Samah, Irza; Harith Amlus, Mohammad (International Journal of Psychosocial Rehabilitation, 2020)
This project is to find out the determinants of rotation among employees in educational organizations. Organizations will understand more about job rotation and its benefit to the organization. Other than that, it’s useful for management of staff from educational organizations. Job rotation is essential for management in organizations, especially for staff from educational organizations. Job rotation will help managers explore the hidden talent of employees. Other than that, job rotation is designed to expose employees to a wider range of operations in order to assist managers in exploring their hidden talent. In the process of job rotation. They will be exposed to different tasks and get the hang of new working environments. Therefore, it is important to determine the determinant of job rotation in an organization. This can help the organization to make improvements in performance and also skill and knowledge. The scope of this study covers the determinants of job rotation among employees in educational organizations. This project will be carried out based on the employees of the educational organization. Data collection methods are used, including disseminating distributed questionnaires to randomly selected employees. 400 questionnaires have been distributed to employees for surveys of employee determinants among employees in educational organizations. Employees’ responses on questionnaires related to job rotation determinants among officers in educational organizations were analyzed using the Statistical Package Social Sciences (SPSS) software, and the results will be indicated in this study.